Parliament Buildings and the Sinking of the Titanic - Kernohan, David (Architectural History Aotearoa, 2004)
The RMS Titanic was the ultimate symbol of the power and ubiquitousness of the British Empire. Everything was in the finest Edwardian Classic style. The public rooms were sumptuous with a grand Baroque stairway leading into the Grand Salon. There was the first-ever on board swimming pool, a Palm Court, a Parisian Café and a lounge modelled after a room at the Palace of Versailles. On the evening of 14 April, 1912, the ship hit an iceberg. It took two hours and 40 minutes after hitting the floating ice for the ship to go down. Construction of the Parliament Buildings in Wellington began in 1912. The finally approved design was an amalgamation of the winning competition entry of John Campbell and Claude Paton and the fourth placed design by Campbell and Lawrence. The design was in the distinct Edwardian Classic image of the British Empire but with only a little of the exuberance of some of Campbell’s Imperial Baroque work. Interestingly, the building displayed some New Zealand character, most notably in the use of materials and in the Māori Affairs Committee Room. The building was not completed, half finished, until 1922. This paper discusses the nature of the entries to the Parliament Building competition and the politics surrounding the event. It focuses on the architecture of John Campbell, most notably his affinity for the Edwardian Classical style. The paper explores the significance of the style in the New Zealand context and conjectures on other influences that might have held some sway. Finally, the paper suggests the building might have benefited from suffering a fate similar to that of the Titanic.